Effects of Melatonin Supplementation on Hormonal, Inflammatory, Genetic, and Oxidative Stress Parameters in Women With Polycystic Ovary Syndrome - Jamilian, Mehri; Foroozanfard, Fatemeh; Mirhosseini, Naghmeh; Kavossian, Elham; Aghadavod, Esmat; Bahmani, Fereshteh; Ostadmohammadi, Vahidreza; Kia, Mersedeh; Eftekhar, Tahereh; Ayati, Elnaz; Mahdavinia, Mostafa; Asemi, Zatollah (Frontiers in Endocrinology, 2019)
Purpose: The aim of the current study was to evaluate the effect of melatonin administration on clinical, hormonal, inflammatory and genetic parameters in women with PCOS. Methods: The present randomized, double-blinded, placebo-controlled clinical trial was conducted among 56 patients with PCOS, aged 18-40 years old. Subjects were randomly allocated to take either 5 mg melatonin supplements (n=28) or placebo (n=28) twice a day for 12 weeks. Results: Melatonin administration significantly reduced hirsutism (β -0.47; 95% CI, -0.86, -0.09; P=0.01), serum total testosterone (β -0.11 ng/mL; 95% CI, -0.21, -0.02; P=0.01), high-sensitivity C-reactive protein (hs-CRP) (β -0.61 mg/L; 95% CI, -0.95, -0.26; P=0.001) and plasma malondialdehyde (MDA) levels (β -0.25 µmol/L; 95% CI, -0.38, -0.11; P<0.001), and significantly increased plasma total antioxidant capacity (TAC) levels (β 106.07 mmol/L; 95% CI, 62.87, 149.28; P<0.001) and total glutathione (GSH) (β 81.05 µmol/L; 95% CI, 36.08, 126.03; P=0.001) compared with the placebo. Moreover, melatonin supplementation downregulated gene expression of interleukin-1 (IL-1) (P=0.03) and tumor necrosis factor alpha (TNF-α) (P=0.01) compared with the placebo. Conclusions: Overall, melatonin administration for 12 weeks to women with PCOS significantly reduced hirsutism, total testosterone, hs-CRP and MDA, while increased TAC and GSH levels. In addition, melatonin administration reduced gene expression of IL-1 and TNF-α.